A new low‐firing and high‐Q microwave dielectric ceramic Li9Zr3NbO13. Issue 6 (30th January 2018) - Yang, Han; Tang, Bin; Fang, Zixuan; Luo, Jun; Zhang, Shuren
Abstract: The microwave dielectric ceramic Li9 Zr3 NbO13 was found and investigated. Prepared via the solid‐state reaction method, the Li9 Zr3 NbO13 formed as a Li2 ZrO3 ‐type solid solution at 880‐900°C, with monoclinic structure in C2/c space group and Z = 4. Typically, the Li9 Zr3 NbO13 sintered at 900°C exhibited the excellent microwave dielectric properties of ε r = 21.3, Q × f = 43 600 GHz (at 7.4 GHz), τ f = 7.3 ppm/°C.